Evaluación de la ginogénesis de la Trucha (oncorhynchus mykiss) en San Miguel de Otongorito de la ciudad de Quito. - Analuisa Tonato, Edwin Armando (2021)
The cultivation of rainbow trout (Oncorhynchus mykiss), in national farms at all levels, has become one of the most important fish species cultivated in Ecuador, and precisely to obtain the best results not only in meat production but over time. They look out the need to invest in young fish that are 100% for females and quickly achieve the ideal weight is from 6 months old. In this aspect is where the importance and profitability of trout farming lies, since having male trout negatively affects due to its decrease in aggressiveness and other growth. The gynogenesis technique is based on the exclusive transfer of genetic information only from the mother, this due to the fact that the paternal genome is inactivated through the use of UV radiation, and then fertilization and shock are applied to the eggs. Prevent the expulsion of the second polar body during the second mitosis and thus obtaining diploid individuals. Taking into consideration that fact, this research work proposed to apply the gynogenesis technique or zootechnical parameters to obtain and confirm the production of 100% female fingerlings. The investigation demonstrated and confirmed that the results applied treatment 4 (final shock of 27°C for 15 minutes) reaches or allows to obtain the highest percentage of female fingerlings, likewise statistical differences (p <0.005) related to several indicators or variables studied such as the number of female or gynogenetic fingerlings obtained, the increase in weight, length, and finally survival after the application of the gynogenesis technique.